Chalaropsis pruni sp. nov. (Ceratocystidaceae), a new species from Prunus serrulata var. pubescens in South Korea - Cho, Sung-Eun; Seo, Sang-Tae; Nam, Youngwoo; Wingfield, Michael J.; Lee, Dong-Hyeon (Phytotaxa, 2024)
A routine survey in a natural forest located in the Gangwon Province of Korea was undertaken in 2022 to establish an inventory of potentially pathogenic fungi that might affect tree health in the country. An ophiostomatoid fungus was consistently isolated from naturally occurring wounds on Prunus serrulata var. pubescens. Isolates were subjected to morphological and DNA sequence comparisons. The results showed that the fungus resided in a distinct taxonomic lineage, and the novel species is described here as Chalaropsis pruni sp. nov.